2015
DOI: 10.3906/sag-1310-63
|View full text |Cite
|
Sign up to set email alerts
|

Effects of contemporary orthodontic composites on tooth color following short-term fixed orthodontic treatment: a controlled clinical study

Abstract: IntroductionOrthodontics is a unique science in dentistry since its workspace sets on the external surface of enamel when using fixed appliances for treatment. Orthodontists or patients may encounter unwanted changes on the enamel surface or structure, such as discoloration, white spots, microcracks, fractures, and abrasions during and after fixed orthodontic treatment (FOT) because of, e.g., diet, oral care, bonding materials and techniques, composites, appliances, debonding, and clean-up procedures (1-3). Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 24 publications
1
13
0
5
Order By: Relevance
“…Irrespective of these conflicting conclusions, several reports have emphasized the need for further randomized clinical trials to try to clarify the issue. In vivo studies have previously revealed colour differences following orthodontic treatment, but such colour changes were not always clinically visible …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Irrespective of these conflicting conclusions, several reports have emphasized the need for further randomized clinical trials to try to clarify the issue. In vivo studies have previously revealed colour differences following orthodontic treatment, but such colour changes were not always clinically visible …”
Section: Discussionmentioning
confidence: 99%
“…Relatively few studies have dealt with the evaluation of tooth colour alterations relating to comprehensive orthodontic treatment. These have reported that the CIE* colour parameters of enamel demonstrate significant differences in the period just after the removal of fixed orthodontic appliances . However, it appears that such changes are not consistently clinically discernible …”
Section: Introductionmentioning
confidence: 99%
“…Sabit ortodontik tedaviye bağlı mine yüzeyinde gözlenen renk değişimlerinde bonding materyalleri ve tekniği, kompozit adezivler, debonding ve artık adeziv temizleme yöntemleri, hasta diyeti ve oral hijyen alışkanlıklarının etkili olduğu belirtilmektedir. 1,2 Bu faktörlerden ise bonding materyalleri ve kompozit adezivlerin daha önemli olduğu ifade edilmektedir. 1,3 Asitle pürüzlendirme tekniğinin tanıtımından sonra sabit ortodontik ataşmanlar adezivler aracılığıyla doğrudan mine yüzeyine yapıştırılmaktadır.…”
Section: Introductionunclassified
“…1,2 Bu faktörlerden ise bonding materyalleri ve kompozit adezivlerin daha önemli olduğu ifade edilmektedir. 1,3 Asitle pürüzlendirme tekniğinin tanıtımından sonra sabit ortodontik ataşmanlar adezivler aracılığıyla doğrudan mine yüzeyine yapıştırılmaktadır. 4 Kullanılan asit türüne ve konsantrasyonuna, asitleme süresine ve dişler arasındaki farklılıklara bağlı olarak mine yapısındaki rezin tagların penetrasyon derinliklerinin değiştiği belirtilmektedir.…”
Section: Introductionunclassified
See 1 more Smart Citation